Tracing chalcolithic population mobility using strontium isotopes and proteomics at Gumelnița site, Romania - Tafani, Aurélien; Greco, Enrico; Tykot, Robert H; Barbieri, Pierluigi; Gaspari, Marco; Gabriele, Caterina; Toma, Andreea; Culea, Mihaela; Manea, Bogdan; Darie, Adelina; Opriș, Vasile; Ignat, Theodor; et al. (Scientific reports, 2025)
The Kodjadermen-Gumelnița-Karonovo VI human group (KGK VI) reached its maximal extension around 4500 BC, covering a large area comprised between southern Ukraine and northern Greece. Afterward, its distribution gradually receded, before vanishing altogether at the end of the fifth - early fourth millenniums BC. This study seeks to investigate the role of individual mobility during this process by performing strontium isotopic analyses on the human remains found at Gumelnița, Romania. It provides 87Sr/86Sr values for 21 human tooth enamel samples from 17 different individuals, together with those of 60 plant samples from 20 different locations (15 in Romania and 5 in Bulgaria) that were used to create a bioavailable strontium (BASr) baseline of the region. To obtain reliable sex estimations, proteomic analysis of amelogenin of human tooth enamel were also performed on seven individuals. According to the results, four individuals, three females and one male, should be considered as non-local, and may have spent their childhood on the southern bank of the Danube River. These data suggest that individual mobility was particularly prevalent during the last centuries of the fifth millennium, when the KGK VI complex was undergoing a process of disintegration. Main Text.
Keywords: Humans; Strontium Isotopes; Population Dynamics; Proteomics; Eneolithic; Female; Strontium isotopes; Amelogenin; lidé; dějiny starověku; proteomika; Rumunsko; populační dynamika; zubní sklovina; ženské pohlaví; Male; Romania; izotopy stroncia; History, Ancient; amelogenin; Dental Enamel; mužské pohlaví; Human Migration; migrace lidstva